2009
DOI: 10.1002/mats.200900006
|View full text |Cite
|
Sign up to set email alerts
|

Compartmentalization in NMP in Dispersed Systems: Relative Contributions of Confined Space Effect and Segregation Effect Depending on Nitroxide Type

Abstract: Modeling and simulations employing modified Smith‐Ewart equations have been performed to elucidate compartmentalization effects (the segregation effect and the confined space effect) in nitroxide‐mediated polymerization of styrene at 125 °C in dispersed systems using the nitroxides TEMPO and TIPNO. By proper choice of particle size, it is possible to improve both the level of control and livingness relative to the corresponding homogeneous (bulk/solution) systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(43 citation statements)
references
References 31 publications
5
38
0
Order By: Relevance
“…Smaller k 2 /k t means bimolecular termination is significant, forming a larger number of trapping agents faster. Significant bimolecular termination is not suitable for the controlled RDRP, however, k 2 /k t -value as small as 1.24 × 10 −3 is reported for 2,2,5-trimethyl-4-phenyl-3-azahexane-3-oxy (TIPNO)/styrene system [29]. Figure 12 shows that the acceleration is significant for smaller k 2 /k t -values.…”
Section: Figure 12mentioning
confidence: 99%
“…Smaller k 2 /k t means bimolecular termination is significant, forming a larger number of trapping agents faster. Significant bimolecular termination is not suitable for the controlled RDRP, however, k 2 /k t -value as small as 1.24 × 10 −3 is reported for 2,2,5-trimethyl-4-phenyl-3-azahexane-3-oxy (TIPNO)/styrene system [29]. Figure 12 shows that the acceleration is significant for smaller k 2 /k t -values.…”
Section: Figure 12mentioning
confidence: 99%
“…CLRP in dispersed systems14, 15 can under certain circumstances be strongly influenced by the phenomenon of compartmentalization, which refers to the physical isolation of reactants in discrete confined spaces, i.e., the monomer droplets or polymer particles. Effects of compartmentalization have been predicted theoretically for NMP,16–24 atom transfer radical polymerization (ATRP),22, 25–28 and reversible addition‐fragmentation chain transfer (RAFT) polymerization,21, 22, 29–32 and experimental evidence is also starting to emerge 33–36. There are two possible distinct effects of compartmentalization: The segregation effect and the confined space effect 14, 18.…”
Section: Introductionmentioning
confidence: 99%
“…The confined space effect refers to how the rate of reaction between two species is higher in a small particle than in a large particle. The confined space effect can cause the rate of deactivation to increase in CLRP systems based on the persistent radical effect (e.g., NMP and ATRP) 18–21, 23–28, 36…”
Section: Introductionmentioning
confidence: 99%
“…Their compartmentalization model, however, was not able to compute the MWD or its averages. In a later work [114], they compared the performance of two mediating agents, TEMPO and TIPNO, on the compartmentalization and livingness of the system. They found that the nature of the nitroxide influenced the minimum particle size beyond which compartmentalization could not be neglected.…”
Section: Nmp In Heterogeneousmentioning
confidence: 99%